2015
DOI: 10.4172/2167-0943.1000181
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome Diagnosed by Three Different Criteria in School-Aged Children from Rural and Urban Areas of Northwest Mexico

Abstract: The International Diabetes Federation (IDF) does not justify the evaluation of metabolic syndrome (MetS) in children aged less than 10 years, unless they have a family history of risk factors. The prevalence of overweight and obesity in the Northwest of Mexico has increased in recent decades, making it possible to consider that MetS is already present in this group of population. Objective:The primary objective of this study was to determine the prevalence of metabolic syndrome in children aged 6 to 9 years li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(43 reference statements)
1
1
0
Order By: Relevance
“…The clinical pattern of elevated triglycerides and low HDL-c (86.7 mg/dL and 37.8 mg/dL) agrees with that reported by Reaven and his co-authors for the Mexican-American school population (84.6 mg/dL and 47 mg/dL) [28] . Additionally, with previous studies carried out in the same region but among school children aged six to twelve, in whom the same pattern of alterations was observed, Ramirez found a similar lipid pattern, characterized by metabolic syndrome, in rural (5%) and urban (7.4%) areas [11] .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation

Cardiovascular and Diabetes Risk in Preschoolers

Martha Nydia Ballesteros-Vásquez,
Saraí García-Gámez,
Elizabeth Artalejo-Ochoa
et al. 2023
CR
“…The clinical pattern of elevated triglycerides and low HDL-c (86.7 mg/dL and 37.8 mg/dL) agrees with that reported by Reaven and his co-authors for the Mexican-American school population (84.6 mg/dL and 47 mg/dL) [28] . Additionally, with previous studies carried out in the same region but among school children aged six to twelve, in whom the same pattern of alterations was observed, Ramirez found a similar lipid pattern, characterized by metabolic syndrome, in rural (5%) and urban (7.4%) areas [11] .…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies by our working group carried out in the Sonora population have confirmed overweight and obesity in children aged six to nine, as well as metabolic syndrome in urban (7%) and rural (5%) areas. Diet and physical inactivity are the two main factors involved [11] .…”
Section: Introductionmentioning
confidence: 99%

Cardiovascular and Diabetes Risk in Preschoolers

Martha Nydia Ballesteros-Vásquez,
Saraí García-Gámez,
Elizabeth Artalejo-Ochoa
et al. 2023
CR